Metaphors of Human-Flora-Fauna Symbiosis: Eco-Critical Discourse Expositions in Yorùbá Proverbial Analysis - Onipede, Festus Moses; Olutoyin, Jaiyeoba Olubunmi (Vivid: Journal of Language and Literature, 2024)
It has been emphasized that metaphors in general are crucial forcomprehending and interpreting ecological discourse. Numerous studieson Yorùbá proverbs have been conducted (Jelili et al., 2022; Akanbi, 2020;Anyachebelu, 2019; Olofinsao, 2018; Faleye, 2018; Ojo, 2015; Akanbi,2015, etc.), but insufficient research has been done on human-flora-faunasymbiosis, particularly in Yorùbá proverbs. This study uses ecocriticalmetaphor analysis to look at the symbiosis of humans, plants, and faunain Yorùbá proverbs. The study focuses on how, according to the Yorùbáworldview, particular plants and animals are used to symbolise varioushuman experiences, actions, and traits in Yorùbá proverbs. We use thetransitivity system from the Systemic Functional Linguistics approach toeco-critical discourse analysis, along with Lakoff and Johnson’s ConceptualMetaphor Theory (CMT) to explore human experiences with naturethrough process types and illustrate the metaphorical “mapping” acrossthe conceptual domain. Other human experiences are conceptualised asthe target domain through the lens of flora and animals, which serve as thesource domain. Both primary and secondary sources of information werecarefully selected for this article. The study discovers that Yorùbá proverbsuse metaphors of animals such as dogs, cows, chameleons, doves, andeagles as well as woods and trees like iróko and mahogany, to warn peopleagainst negative attitudes towards the ecosystem, like destruction, laziness,intolerance, and impatience among others. For harmonious coexistence inthe ecosystem, the proverbs urge humans to behave well toward nature.According to the results of the transitivity analysis, the detected processchoices in the data can be seen as a positive discourse that motivates peopleto conserve the environment.